The Role of Pancasila Values in Facing the Future of Science Education Based on Artificial Intelligence Technology: A Philosophical Perspective - Purmanna, Astrino; Hasanah, Rafiatul; Rofika, Rofika; Mahardika, I Ketut; Waluyo, Joko (International Journal of Education, Information Technology, and Others, 2024)
This research aims to conduct a philosophical review of the role of Pancasila in facing the future of science education based on Artificial Intelligence technology. Given the application of Artificial Intelligence in science education continues to increase so that this can affect new opportunities in supporting the development of science education, learning innovation and present significant challenges. The type of research conducted is qualitative through library research. The results showed that the role of Pancasila ideology towards the application of Artificial Intelligence (AI) can act as an important ethical framework in facing the future of science education. The role of Pancasila as an ethical framework in the use of Artificial Intelligence in science education is to create the use of Artificial Intelligence technology that is more humane, fair, and has a positive impact on the world in general. Other results are detailed in this paper which include the potential and challenges that may arise in integrating the values of Pancasila as an ethical framework in the use of Artificial Intelligence in various fields, especially science education. Based on the findings of this research, it contributes to the view that the role of Pancasila in science education based on Artificial Intelligence technology needs to be understood through a philosophical perspective to ensure its relevance in the future.